2018
DOI: 10.1021/acs.accounts.7b00477
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Real-Time Mechanical and Morphological Characterization of Electrodes for Electrochemical Energy Storage and Conversion by Electrochemical Quartz Crystal Microbalance with Dissipation Monitoring

Abstract: Quartz crystal microbalance with dissipation monitoring (QCM-D) generates surface-acoustic waves in quartz crystal plates that can effectively probe the structure of films, particulate composite electrodes of complex geometry rigidly attached to quartz crystal surface on one side and contacting a gas or liquid phase on the other side. The output QCM-D characteristics consist of the resonance frequency (MHz frequency range) and resonance bandwidth measured with extra-ordinary precision of a few tenths of Hz. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 29 publications
2
97
0
1
Order By: Relevance
“…Excellent reviews on the working principle and data analysis can be found in Dixon (2008), Reviakine et al (2011), Johannsmann (2015. In the last decade, QCM-D has been successfully used in biotechnology and environmental science as a tool for investigating the structure and mechanics of soft and solvated interfaces (Dixon, 2008;Kanazawa and Cho, 2009;Campos et al, 2015), as well as hydrodynamic phenomena in non-uniform nanostructured surfaces (Shpigel et al, 2018). It has been particularly relevant in the field of lipid biophysics, as a useful technique to understand the kinetics of formation of supported lipid bilayers (Keller and Kasemo, 1998;Richter et al, 2003;Cho et al, 2010;Lind and Cárdenas, 2016), and their interactions with relevant biomolecules (Mechler et al, 2007;Michanek et al, 2010;Nielsen and Otzen, 2013).…”
Section: Qcm-d and Lipid Membrane Phase Behaviormentioning
confidence: 99%
“…Excellent reviews on the working principle and data analysis can be found in Dixon (2008), Reviakine et al (2011), Johannsmann (2015. In the last decade, QCM-D has been successfully used in biotechnology and environmental science as a tool for investigating the structure and mechanics of soft and solvated interfaces (Dixon, 2008;Kanazawa and Cho, 2009;Campos et al, 2015), as well as hydrodynamic phenomena in non-uniform nanostructured surfaces (Shpigel et al, 2018). It has been particularly relevant in the field of lipid biophysics, as a useful technique to understand the kinetics of formation of supported lipid bilayers (Keller and Kasemo, 1998;Richter et al, 2003;Cho et al, 2010;Lind and Cárdenas, 2016), and their interactions with relevant biomolecules (Mechler et al, 2007;Michanek et al, 2010;Nielsen and Otzen, 2013).…”
Section: Qcm-d and Lipid Membrane Phase Behaviormentioning
confidence: 99%
“…Recently, a real breakthrough in the microgravimetric analysis of the battery electrode interfaces has been achieved by applying QCM in combination with dissipation monitoring. Using this set‐up in a multiharmonic mode the mechanical properties of Sn/electrolyte interface and the viscoelastic behavior of Li 4 Ti 5 O 12 and LiFePO 4 composite electrode coatings are revealed . Nevertheless, the in‐situ analysis of SEI formation and its mechanical properties is limited only to Sn/electrolyte and Li 4 Ti 5 O 12 /electrolyte interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Using this set-up in a multiharmonic mode the mechanical properties of Sn/electrolyte interface and the viscoelastic behavior of Li 4 Ti 5 O 12 and LiFePO 4 composite electrode coatings are revealed. [16][17][18][19] Nevertheless, the in-situ analysis of SEI formation and its mechanical properties is limited only to Sn/electrolyte and Li 4 Ti 5 O 12 /electrolyte interfaces. Hence, there is a large application window of this methodology for characterizing the mechanical and morphological properties of the SEI layer deposited under the influence of various functional additives.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the ZnO nanostructures grown on the graphene, where only upper graphene surface is available to electrolyte, a thin layer of graphene covered ZnO nanostructures is postulated to provide higher number of electroactive sites for charge storage due to the accessibility of both surfaces (upper and lower) to electrolyte, allowing for more effective charge and mass exchange. The study of such architectures with coupled methods such as coupling electrochemistry with gravimetric analysis, i.e., quartz crystal microbalance (QCM) can significantly contribute to their further development.Electrochemical quartz crystal microbalance (EQCM) has developed into a powerful in situ technique to measure ionic fluxes in different electrochemical systems, [18][19][20][21][22][23][24] in which not only the current response (ΔI) but also the in situ capturing of global gravimetric change (Δm) at the electrode/electrolyte interface is The present work is on the synthesis and characterization of vertically aligned ZnO nanostructures sheltered by electrochemically reduced graphene oxide (ERGO), i.e., ZnO@ERGO, which are directly generated on quartz resonators of microbalance sensors. [3] However, fundamental importance of the ionic flux into the electrode, which plays an essential role in understanding the charge-storage mechanism of a specific electrochemical system is generally underestimated.…”
mentioning
confidence: 99%
“…Electrochemical quartz crystal microbalance (EQCM) has developed into a powerful in situ technique to measure ionic fluxes in different electrochemical systems, [18][19][20][21][22][23][24] in which not only the current response (ΔI) but also the in situ capturing of global gravimetric change (Δm) at the electrode/electrolyte interface is The present work is on the synthesis and characterization of vertically aligned ZnO nanostructures sheltered by electrochemically reduced graphene oxide (ERGO), i.e., ZnO@ERGO, which are directly generated on quartz resonators of microbalance sensors. The vertical orientation of the ZnO nanorods is achieved by a two-step synthesis method involving an electrochemically grown seed layer and a subsequent hydrothermal growth.…”
mentioning
confidence: 99%